2024
DOI: 10.3390/jcm13030744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of COVID-19 Effect on Mental Health, Self-Harm, and Suicidal Behaviors in Children and Adolescents Population

Jagoda Grzejszczak,
Dominik Strzelecki,
Agata Gabryelska
et al.

Abstract: Objectives: The impact of the COVID-19 pandemic on the psychological state of the under-18 population includes an increased risk of psychopathological symptoms development and exacerbation of already present psychiatric disorders. This study aimed to assess the prevalence of mental health problems in Polish children and adolescents with a focus on suicidal and self-harm behavior with the impact of the pandemic. Methods: The questionnaire collected demographic data, information regarding mental states and psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…As such, the DBT-A treatment received during this period of time was sub-optimal and could have affected treatment results leading to a lack of improvement in the secondary outcomes. Additionally, several studies have demonstrated an increase in various mental health symptoms in general, and in self-harm among adolescents in particular during the COVID-19 pandemic [43,44]. It is possible that this could have affected the adolescents in our study that received DBT-A treatment during the pandemic even though no differences in self-harm was found between participants pre-and during the pandemic.…”
Section: Discussionmentioning
confidence: 80%
“…As such, the DBT-A treatment received during this period of time was sub-optimal and could have affected treatment results leading to a lack of improvement in the secondary outcomes. Additionally, several studies have demonstrated an increase in various mental health symptoms in general, and in self-harm among adolescents in particular during the COVID-19 pandemic [43,44]. It is possible that this could have affected the adolescents in our study that received DBT-A treatment during the pandemic even though no differences in self-harm was found between participants pre-and during the pandemic.…”
Section: Discussionmentioning
confidence: 80%
“…No estudo realizado por (Grzejszczak et al, 2024) evidenciou-se que no grupo tanto de crianças como de adolescentes houve aumento dos sintomas depressivos e ansiosos. Além disso, foi identificado aumento dos comportamentos de automutilação nos adolescentes incluídos no trabalho, já no grupo de crianças abaixo de 12 anos ocorreu um aumento acentuado no pensamento de morte.…”
Section: Discussionunclassified